Soluble Receptor Isoform of IFN-Beta (sIFNAR2) in Multiple Sclerosis Patients and Their Association With the Clinical Response to IFN-Beta Treatment - Aliaga-Gaspar, Pablo; Hurtado-Guerrero, Isaac; Ciano-Petersen, Nicolas Lundahl; Urbaneja, Patricia; Brichette Mieg, Isabel; Virginia Reyes, Virginia; Rodríguez-Bada, José Luis; Alvarez-Lafuente, Roberto; Arroyo, Rafael; Quintana, Ester; Ramió-Torrentà, Lluis; Alonso, Ana; et al. (Frontiers, 2021)
Protein and mRNA levels of sIFNAR2 increased after IFN-b treatment. According to the clinical response, only non-responders increased sIFNAR2 significantly at both protein and mRNA levels. sIFNAR2 gene expression correlated with the transmembrane isoform expression and was 2.3-fold higher. While MxA gene expression increased significantly after treatment, IFNAR1 and IFNAR2 only slightly increased. After short-term IFN-b in vitro induction of PBMC, 6/7 patients increased the sIFNAR2 expression. IFN-b administration induces the production of sIFNAR2 in RRMS and higher levels might be associated to the reduction of therapeutic response. Thus, levels of sIFNAR2 could be monitored to optimize an effective response to IFN-b therapy.
Keywords: Receptores - Efectos de los medicamentos; Interferón; IFNAR; Alternative splicing; Soluble receptors; Interferon beta; Multiple sclerosis